Interleaved switched-capacitor bidirectional DC-DC converter with wide voltage-gain range for energy storage systems - Zhang, Yun; Gao, Yongpin; Li, Jing; Sumner, Mark (IEEE, 2017)
In this paper, an interleaved switched-capacitor bidirectional DC-DC converter with a high step-up/step-down voltage gain is proposed. The interleaved structure is adopted in the low-voltage side of this converter to reduce the ripple of the current through the low-voltage side, and the series-connected structure is adopted in the high-voltage side to achieve the high step-up/step-down voltage gain. In addition, the bidirectional synchronous rectification operations are carried out without requiring any extra hardware, and the efficiency of the converter is improved. Furthermore, the operating principles, voltage and current stresses, and current ripple characteristics of the converter are analyzed. Finally, a 1kW prototype has been developed which verifies a wide voltage-gain range of this converter between the variable low-voltage side (50V-120V) and the constant high-voltage side (400V). The maximum efficiency of the converter is 95.21% in the step-up mode and 95.30% in the step-down mode. The experimental results also validate the feasibility and the effectiveness of the proposed topology.